Cultural Heritage Sites as Learning Resources: Innovations in the Madrasah Operational Curriculum (KOM) at Madrasah Ibtidaiyah - Marduati, Marduati; Mawardi, Mawardi; Simehate W, Adelia; Faizurrahman, Sayyid (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2024)
This study aims to explore the potential of cultural heritage as a learning resource in the Madrasah Operational Curriculum (KOM) in Madrasah Ibtidaiyah. Innovation in cultural heritage-based learning can enrich the teaching and learning process by integrating direct experience in the field, thereby increasing students' understanding of the subject matter. This study uses a descriptive qualitative approach with observation, interview, and documentation methods to collect data. The results, indicates that the use of cultural heritage in KOM contributes to strengthening basic competencies, developing 21st century skills, and preserving local culture. This is in accordance with the mandate of the independent curriculum to utilize social and natural wealth as a learning resource, which is stated in the madrasah operational curriculum implementation policy. This implementation also requires support from teachers, a flexible curriculum, and collaboration with local communities and the government. The use of cultural heritage in learning also has an impact on increasing students' competence in understanding history related to their region. This study recommends a cultural heritage-based learning model as a strategic step to improve the quality of education in Elementary Madrasah while promoting cultural preservation.Keyword: Elementary madrasah, KOM, cultural heritage.